2015
DOI: 10.4103/0366-6999.160521
|View full text |Cite
|
Sign up to set email alerts
|

Are There Any Clinical and Radiographic Differences Between Quadriceps-sparing and Mini-medial Parapatellar Approaches in Total Knee Arthroplasty After a Minimum 5 Years of Follow-up?

Abstract: Background:Although the early clinical outcomes of total knee arthroplasty (TKA) using minimally invasive surgery techniques have been widely described, data on the mid- to long-term outcomes are limited. We designed a retrospective study to compare the two most common TKA techniques – The modified quadriceps-sparing (m-QS) approach and the mini-medial parapatellar (MMP) approach – In terms of the clinical and radiographic parameters, over a minimum follow-up period of 5 years.Methods:The m-QS approach was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A total of 1678 relevant studies were obtained in the initial search of the PubMed (n = 190), EMBASE (n = 477), Cochrane Library (n = 531), and Web of Science (n = 460) databases, as well as from manual retrieval (n = 20). After excluding duplicate literature and applying the inclusion criteria and exclusion criteria, 51 RCTs 15, were finally included in this study, of which 42 15,[29][30][31][32][33][34][35][36][37][39][40][41][42][43][44][45][46][47][49][50][51][52][53][54][55][56][57][58][59][62][63][65][66][67][70][71][72][73][74][75][76] were clearly approved by ethics committees, while the approval of nine was not reported. Two three-arm tests were included in the analysis, while the remainder were all two-arm tests.…”
Section: Literature Screening Process and Resultsmentioning
confidence: 99%
“…A total of 1678 relevant studies were obtained in the initial search of the PubMed (n = 190), EMBASE (n = 477), Cochrane Library (n = 531), and Web of Science (n = 460) databases, as well as from manual retrieval (n = 20). After excluding duplicate literature and applying the inclusion criteria and exclusion criteria, 51 RCTs 15, were finally included in this study, of which 42 15,[29][30][31][32][33][34][35][36][37][39][40][41][42][43][44][45][46][47][49][50][51][52][53][54][55][56][57][58][59][62][63][65][66][67][70][71][72][73][74][75][76] were clearly approved by ethics committees, while the approval of nine was not reported. Two three-arm tests were included in the analysis, while the remainder were all two-arm tests.…”
Section: Literature Screening Process and Resultsmentioning
confidence: 99%
“…Notably, Heekin [49] and Sun [48] reported significant better quadricep strength in the mini-MV group as measured by Cybex testing and straight leg raise whereas Zhang [47] and Liu [44] did not. In terms of QS vs. mini-MPP, Hung et al reported no significant difference in any of the clinical (VAS, KSS, ROM) and radiographic outcomes after a minimum of five years of follow-up [50,51]. Lin reported similar results with a shorter follow-up from postoperative 24 hours to two years [12].…”
Section: Discussionmentioning
confidence: 98%
“…[23][24][25] Currently, many well-designed studies have tried to demonstrate the advantages/disadvantages, the clinical results and the complications of the MIS approaches compared to the MPP approach. [26][27][28][29] In this article we will review the current literature (based on randomized controlled trials (RCTs), systematic reviews and meta-analyses) on MIS compared to traditional approach and analyse their clinical safety, efficacy and long-term results.…”
Section: Introductionmentioning
confidence: 99%